Penerapan Metode Analytic Hierarchy Process (AHP) dalam Pengambilan Keputusan Perekrutan Tenaga Kesehatan - Hilmansyah Gani; Mohamad Ilyas Abas; Irawan Ibrahim; Alter Lasarudin; Yulanda Yunus (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The importance of healthcare professionals in ensuring that patients always receive the best care makes hospitals meticulous in selecting their workforce. When choosing healthcare professionals, subjective factors often come into play, as these factors have not been well-defined in the decision-making process when evaluating potential healthcare workers. Therefore, it is possible for hospitals to make mistakes in selecting potential healthcare professionals, and this can have significant implications for the hospital. Consequently, it is necessary to adhere to established criteria when selecting future healthcare workers. Moreover, the defined criteria and the manual calculation of criteria by the hospital further require a considerable amount of time to make accurate decisions. The objective of this research is to develop a website-based system that can assist the UPT. RSUD Mokoyurli Buol in making quick and accurate decisions in selecting healthcare personnel. The Decision Support System (DSS) is a system that can solve ranking problems quickly and determine the highest to lowest values in a selection process. The final outcome of this research is a system that can make decisions in selecting hospital staff using the Analytic Hierarchy Process (AHP) method. Black box testing ensures the compatibility of the application's functional events, while white box testing verifies the internal logic of the system. Therefore, it can be concluded that the system's logic functions effectively.